PROBLEMA AGRARIA DI MASA MENDATANG - Surahman Surahman (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2005)
The National wealth is the final destination of the management of the agrarian objects. It is also the mercy which people should thank. It is also an eternal relationship beetwen people and God